2018
DOI: 10.1136/bcr-2018-226264
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous resolution of a ‘ping-pong’ fracture at birth

Abstract: ‘Ping-pong’ fractures are depressed skull fractures in newborn infants that occur as inward buckling of the calvarial bones, forming a cup shape. These fractures are often associated with maintenance of bone continuity. These fractures may occur spontaneously during the intrauterine period or secondary to birth trauma. Currently, there is no standard protocol for the management of depressed skull fractures. Neurosurgical or non-surgical approaches may be administered depends on the severity of the fracture. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
6
0
4
Order By: Relevance
“…The three patients in our sample who experienced skull fractures at the time of delivery had fracture depths ranging from 8 to 16 mm. As reported in the literature, skull fractures at the time of birth can occur as a result of the head pressing into the maternal pelvis or from the use of surgical instruments to deliver the neonate [ 7 ]. However, we did not find any literature reporting that skull fractures caused by birth trauma tend to be deeper than those resulting from falls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three patients in our sample who experienced skull fractures at the time of delivery had fracture depths ranging from 8 to 16 mm. As reported in the literature, skull fractures at the time of birth can occur as a result of the head pressing into the maternal pelvis or from the use of surgical instruments to deliver the neonate [ 7 ]. However, we did not find any literature reporting that skull fractures caused by birth trauma tend to be deeper than those resulting from falls.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional treatments for ping pong fractures include surgical repair or observation for spontaneous improvement over time. Recently, vacuum-assisted elevation has been described as a viable treatment option [ 5 7 ]. Multiple studies have shown that the following scenarios may necessitate surgical repair: the presence of a foreign body, debris, or infected tissue in a wound, cerebrospinal fluid leak, presence of a hematoma, increased intracranial pressure, neurological impairment, esthetic considerations, and presence of a hygroma [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Algunos autores recomiendan seguimiento clínico; de hecho, se han reportado casos de resolución espontánea de la lesión. [5][6][7] Una conducta alternativa favorece la corrección quirúrgica, 1,2,8 cuyas indicaciones son lesiones asociadas a la fractura (presencia de hemorragia encefálica, contusión cerebral o fragmentos óseos), signos de foco neurológico asociado a la fractura, hipertensión endocraneal, gran defecto estético o lesiones de gran tamaño (más de 5 mm de profundidad y/o más de 2 cm de largo) por el riesgo de compresión cerebral y aparición de convulsiones. 9 En ausencia de estas indicaciones, hay autores que recomiendan esperar desde días hasta meses luego del diagnóstico a fin de realizar la corrección quirúrgica.…”
Section: Discussionunclassified
“…Complications include subdural or epidural hematomas, cerebral contusions, parenchymal lesions, or neurological sequelae, especially in compound depressed fractures. 11 Regarding their management, the decision on the procedure corresponds to the neurosurgeon; conservative and expectant management may be considered in the case of simple and shallow fractures, which may resolve spontaneously. In other cases, such as that of the patient described here, the manual aspiration reduction system (MARS) can be used, a simple suction method that is accessible, effective, safe, low-cost, and non-surgical.…”
Section: MMmentioning
confidence: 99%
“…8 In the case of more complex fractures, surgical treatment by craniotomy may be required. [9][10][11][12][13] Ilhan described the case of a male infant born at 39 weeks of gestation with a birth weight of 3250 g from a controlled pregnancy and with no history of trauma. At birth, he had an Apgar score of 8/9, a skull circumference of 35 cm (p 50-75) and a depression in the right parietal region that measured 3 × 3 cm and had a depth of 4 mm without other signs or symptoms.…”
Section: MMmentioning
confidence: 99%